The Use of Digital Technology for Educational Institution Administration under the Sakaeo Primary Educational Service Area Office 2 - Kunpoon, Chotiphat; การีเวท สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were to: 1) investigate the use of digital technology for school administration under the Sa Kaeo Primary Educational Service Area Office 2, 2) to compare the use of digital technology for school administration classified by gender, position, educational level, work experience, and school size, and 3) to propose guidelines for developing the use of digital technology for school administration. The sample consisted of 296 teachers under the Sa Kaeo Primary Educational Service Area Office 2, determined using the Krejcie and Morgan table (Krejcie & Morgan, 1970: 608) and selected through stratified random sampling. The research instrument for data collection was a 5-level rating scale questionnaire with the Index of Item-Objective Congruence (IOC) ranging from 0.87 to 1.00 and an overall reliability of 0.98. The statistics used for data analysis included frequency, percentage, mean, standard deviation, t-test, and F-test. The research findings revealed that: 1. The use of digital technology for school administration under the Sa Kaeo Primary Educational Service Area Office 2, overall, was practiced at a high level (= 4.14, S.D. = 0.406). When considering each aspect, it was found that the aspect with the highest level of practice was general administration (= 4.44, S.D. = 0.493), followed by academic administration (= 4.25, S.D. = 0.561) and personnel administration (= 4.01, S.D. = 0.654), respectively. The aspect with the lowest level of practice was budget administration (= 4.01, S.D. = 0.708). 2. The comparison of the use of digital technology for school administration showed that teachers with different positions had significantly different usage of digital technology at the 0.05 statistical level, whereas there were no significant differences based on gender, educational level, work experience, and school size. 3. Regarding the guidelines for developing the use of digital technology for school administration, synthesized from the research findings, the researcher proposed the following guidelines ordered by the importance of the results: 1) General Administration: It should be elevated to a Smart Office by using an electronic document system (E-Saraban) for the systematic receiving, sending, and storing of documents. Applications and social media should be the main channels for internal communication, coordination, and public relations with the community and parents. This includes using technology for building and facility management as well as school safety. 2) Academic Administration: The use of digital platforms for full-scale curriculum and learning management systems (LMS) should be promoted. An online learning media repository (Digital Content Bank) should be developed for teachers to easily exchange and access resources. Furthermore, an information database system (Big Data) should be utilized to analyze individual learners for effective measurement and evaluation, and online professional learning communities (Online PLC) should be supported. 3) Personnel Administration: The personnel database system should be developed into a Single Database connecting personal history, self-development, and performance records. Digital literacy for teachers and staff should be continuously promoted and developed through E-Training systems. Additionally, digital technology should be implemented in performance appraisal and academic standing promotion systems (Digital Performance Appraisal) to ensure transparency and fairness. 4) Budget Administration: The use of Cloud Accounting should be pushed forward to keep data updated and verifiable in real-time. The budget disbursement process should be transformed into a full E-Payment system to reduce the risk of using cash. An information summary screen (Dashboard) should be created to track budget status, enabling administrators to make accurate and swift financial planning decisions.